What Drives B-to-B Customers' Adoption of Smart Product-Service Systems? - Eva Kropp; Dirk Totzek (Marketing Review St.Gallen, 2020)
The Internet of Things is associated with a high revenue potential. However, its implementation and associated smart product-service offerings are still in the early stages. This article identifies the key adoption drivers and barriers on the part of B-to-B customers and highlights the strong influence of external pressure on the adoption of smart product-service systems.
Keywords: 650